Kashmir : colonialism and response - Gilani, Sayyid Muhammad Yunus (2012)
Kashmir (formally and officially the state of Jammu and Kashmir) like Malaya ( now Malaysia) became a part of the Muslim World as late as 14th century C E when all its South Asian and the Central Asian neighbors had been the part and parcel of the Ummah for centuries together almost since the first Islamic century. Kashmir under the local Sultans (1325-1585), the Mughals of Hindustan (1586-1752) and the Pathans of Afghanistan (1752-1819) developed into a region, a state and a society with its own peculiar Islamic culture. When most of the Muslim countries were colonized by the Western Powers, Kashmir was colonized by the Sikhs (1819-46) from Punjab and the Hindu Dogra Maharajas (1846-1947). The Muslim Kashmir stood for Islam through the freedom movement during this period. When the movement under the banner of Islam was at its apex and it seemed that the mahkoom (colonized / enslaved) Kashmir was about to achive the goal ,as the British colonies in the Muslim world were getting azadi,merdika ,tahrir and Hurriyat, India ( Bharat ), a newly born nation (Aug 15,1947) invaded it on Oct 27,almost 3 months after her own birth . Since then this newly emerging Eastern expansionist occupying power through its policies of political deceit, cultural aggression, economic onslaught and deIslamizing educational schemes has given rise to the IOK (Indian Occupied Kashmir ). The paper , for obvious reasons narrating the story of the past upto 1988uprising in present tense, throws light on the oppression, persecution and discrimination that the Muslim Kashmir has been witnessing. Alongside the form of freedom movement that followed from 1947 to 1989 is also outlined . In 1989 Jihad Kashmir, a new phase of the movement that invited the attention of the world begins and thus the paper helps to understand the background of the genesis of this new phase.